Developing an Integrated Human Capital Strategy Through OHI-HCM Alignment a Case Study of PT Indopel - Pramadhanty, Alifia Nuzul; Ghazali, Achmad (AFEBI Management and Business Review, 2025)
This research examines the integration of Organizational Health Index (OHI) and Human Capital Maturity (HCM) frameworks in maritime logistics operations. Through analysis of 255 respondents at PT IndoPel, the study identifies critical relationships between organizational health and human capital development. Statistical analysis reveals highest correlations in knowledge management integration (r = 0.84, p < .01) and leadership effectiveness (r = 0.82, p < .01), while identifying significant gaps in workforce optimization (-0.64). These relationships form the foundation for an integrated framework that links organizational health indicators with human capital development outcomes. The framework demonstrates how knowledge management and leadership effectiveness drive capability development in maritime operations, while workforce optimization represents a critical intervention area. This integration provides a structured approach for developing human capital strategies that address both organizational health and capability maturity dimensions, particularly relevant for maritime logistics organizations undergoing transformation.